DAMPAK BANTUAN PKH TERHADAP MASYARAKAT MISKIN DI KELURAHAN BUMI NYIUR KECAMATAN WANEA KOTA MANADO - Setyawardani, Diyah Tri Rezki; Paat, Cornelius J.; Lesawengen, Lisbeth (Universitas Sam Ratulangi, 2020)
The problem of poverty in Indonesia is a social problem that is continually being studied. Indonesia is one of the developing countries because it has various poverty problems such as low income levels, people have difficulty meeting basic needs, education, health, etc, so to overcome the problem of poverty, the role of government is also very necessary. To minimize the problem of social welfare, especially poverty that continues to grow from day to day, the Indonesian government through the Ministry of Social Affairs issued the Family Hope Program (PKH). The Hope Family Program is a policy program formulated by the Government to address the problem of poverty in Indonesia. In other words, the Family of Hope Program is a program of giving cash to Very Poor Families (CBOs) based on the terms and conditions set by carrying out its obligations.Based on research results obtained that the impact of PKH assistance on the poor is twofold namely, positive and negative impacts. For the positive impact of reducing the burden on Very Poor Households (RTSM).to be able to help participating families to pay for education costs and to increase participation in examinations in health and social welfare to ensure nutrition for the elderly and disabled. While the negative impact of the existence of informants who are still dependent or hope for this assistance.Keywords: Family Hope Program (PKH), Poverty, Impact